Social Adequacy Modeling using Resilience Mediated by Academic Adjustment among the Students of Mazandaran University of Medical Sciences - Malihe Talebi Amrei; Nastaran Sharifi; Afsaneh Taheri (Mazandaran University of Medical Sciences, 2021)
Introduction and purpose: Being in sensitive academic conditions often affects students' mental and physical health. This study aimed to model social adequacy using resilience medicated by academic adjustment among the students of Mazandaran University of Medical Sciences, Sari, Iran.   Methods: The statistical population of this descriptive-correlational study consisted of all students studying at Mazandaran University of Medical Sciences in the academic year of 2019-20. A total of 320 students were selected using the stratified sampling method. Data were collected using the Flanner Social Adequacy Questionnaire (1990), Connor-Davidson Resilience scale (2003), as well as Baker and Siryk Academic Adjustment Questionnaire (1989). The obtained data were analyzed using Pearson correlation coefficient and path analysis in SPSS (version 24) and Lisrel (version 8.80) software. Results: The results of path analysis showed that resilience had a direct effect on academic adjustment (ß=0.33, P<0.001) and social adequacy (ß=0.15, P<0.001); moreover, academic adjustment had a direct effect on social adequacy (ß=0.28, P<0.001). Furthermore, academic adjustment played a mediating role in the relationship between resilience and social adequacy. Conclusion: It can be concluded that the social adequacy model using resilience mediated by the academic adjustment among the students of Mazandaran University of Medical Sciences fitted the data well. Considering the role of resilience in increasing academic adjustment and social adequacy, it is of importance to create positive beliefs in health and inform people about the impacts of resilience.